Expert recommendations for diagnosis and treatment of cow’s milk protein allergy in the Colombian pediatric population (2020)
Objective: The objective of this paper is to develop and present recommendations for diagnosis and treatment of Cow’s Milk Protein Allergy (CMPA) which can serve as a reference for pediatric and primary care physicians to consult. Materials and methods: This expert position document was developed by a group of doctors who are specialists in several therapeutic areas who have experience in CMPA. The most relevant topics were defined and a review of the available scientific literature was carried out to prepare a proposal for recommendations that was then discussed by the authors. Results: A position paper was developed that proposes a practical approach to definition, diagnosis and treatment of CMPA in pediatric patients. Conclusions: Early diagnosis and proper management of CMPA can help decrease the burden of this disease and its complications. © 2020 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.